THE EFFECT OF EXTRACTION METHODS ON BANDOTAN LEAF’S (Ageratum conyzoides L) ANTIBACTERIAL ACTIVITY - Aliyah Purwanti (UNIVERSITAS SAM RATULANGI, 2022)
Bandotan leaves (Argentum conizoydes L.) are often called nuisance plants. They grow wild in yards, plantation and fields. The chemical compound in bandotan leaves are potential as an antibacterial agent. The aims are to determine the effect of extraction method, by maceration and soxhletation, on the chemical compounds and antibacterial activity of bandotan leaf extract (Ageratum conizoydes L). Both are using 96% of ethanol. The phytochemical screening showed that both extracts contain alkaloids, flavonoids, tannins, saponins, and steroids, respectively. The photometric analysis showed the average concentration of flavonoids and tannins in bandotan leaf extract resulting from soxhletation, was 177,98 mg/g and 61,13 mg/g, higher than that of maceration, 133,67 mg/g and 47,75 mg/g. The antibacterial activity of extract from soxhletation had a greater inhibitory power 7.524 mm±1.457 compared to the extract from maceration 4.749 mm±2.142. It showed that the extraction method affected the concentration of chemical compounds and antibacterial activity.